Effects of Zinc Pollution and Compost Amendment on the Root Microbiome of a Metal Tolerant Poplar Clone - Guarino, Francesco; Improta, Giovanni; Triassi, Maria; Cicatelli, Angela; Castiglione, Stefano (Frontiers in Microbiology, 2020)
Until recently, many phytoremediation studies were focused solely on a plants ability to reclaim heavy metal (HM) polluted soil through a range of different processes, such as phytoextraction and phyto-stabilization. However, the interaction between plants and their own rhizosphere microbiome represents a new research frontier for phytoremediation. Our hypothesis is that rhizo-microbiome might play a key role in plant wellness and in the response to external stimuli; therefore, this study aimed to shed light the rhizo-microbiome dynamics after an organic amendment (e.g., compost) and/or HM pollution (e.g., Zn), and its relation with plant reclamation ability. To reach this goal we set up a greenhouse experiment cultivating in pot an elite black poplar clone (N12) selected in the past for its excellent ability to reclaim heavy metals. N12 saplings were grown on a soil amended with compost and/or spiked with high Zn doses. At the end of the experiment, we observed that the compost amendment strongly increased the foliar size but did not affect significantly the Zn accumulation in plant. Furthermore, the rhizo-microbiome communities (bacteria and fungi), investigated through NGS, highlighted how α diversity increased in all treatments compared to the untreated N12 saplings. Soil compost amendment, as well as Zn pollution, strongly modified the bacterial rhizo-microbiome structure. Conversely, the variation of the fungal rhizo-microbiome was only marginally affected by soil Zn addition, and only partially impaired by compost. Nevertheless, substantial alterations of the fungal community were due to both compost and Zn. Together, our experimental results revealed that organic amendment increased the bacterial resistance to external stimuli whilst, in the case of fungi, the amendment made the fungi microbiome more susceptible.